2020
DOI: 10.1073/pnas.2014272117
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic effects of forkhead box a2 (FOXA2) and uterine glands on decidualization and fetoplacental development

Abstract: Glands of the uterus are essential for pregnancy establishment. Forkhead box A2 (FOXA2) is expressed specifically in the glands of the uterus and a critical regulator of glandular epithelium (GE) differentiation, development, and function. Mice with a conditional deletion of FOXA2 in the adult uterus, created using the lactotransferrin iCre (Ltf-iCre) model, have a morphologically normal uterus with glands, but lack FOXA2-dependent GE-expressed genes, such as leukemia inhibitory factor (LIF). Adult FOXA2 condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 73 publications
2
24
0
Order By: Relevance
“…Relationships between fetal sex and placental functions have been demonstrated in many studies [ 14 , 15 , 16 , 17 , 18 , 19 ]. Recent study shows that uterine Foxa2 influences the growth of fetus and placenta in a sexual dimorphic manner [ 20 ]. The current study addresses the questions as to whether a uterus lacking Foxa2 has an influence on the transcriptional response of the fetal brain, and whether that influence is conditioned by the fetal sex and placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between fetal sex and placental functions have been demonstrated in many studies [ 14 , 15 , 16 , 17 , 18 , 19 ]. Recent study shows that uterine Foxa2 influences the growth of fetus and placenta in a sexual dimorphic manner [ 20 ]. The current study addresses the questions as to whether a uterus lacking Foxa2 has an influence on the transcriptional response of the fetal brain, and whether that influence is conditioned by the fetal sex and placenta.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous studies, TNFRSF7, a member of tumor necrosis factor-receptor superfamily, is involved in the regulation of T-cell immunity (27). LTF is an important component of non-specific immune system with antimicrobial activity (28). CSF2RB is a paralog of interleukin 2 receptor subunit beta (IL2RB) and could act as receptor of interleukin (IL)-3, IL-5, and granulocytemacrophage colony-stimulating factor (29).…”
Section: Discussionmentioning
confidence: 95%
“…Lymph node metastasis was included in the subsequent study, in which PTPRC expression was found to increase in gastric tumor tissues with lymph node metastasis compared with those tumor tissue without lymph node metastasis (P<0.001) (Figure 9C). Histological type was also an important factor that was found to contribute to the different prognosis performance of gastric cancer patients (28).…”
Section: Ptprc Is Closely Associated With the Pathological Factors Of Gastric Cancermentioning
confidence: 99%
“…LIF is a critical gland specific cytokine expressed in response to nidatory estrogen and is required for embryo implantation in mice (Stewart et al, 1992). Supplementation of recombinant LIF was able to rescue pregnancy in adult FOXA2 cKO mice that contained glands (Kelleher et al, 2017(Kelleher et al, , 2018, however, there were notable effects on the transcriptome of the decidua as well as differences in fetoplacental growth (Dhakal et al, 2020). Integration with published data identified Prss28 and Prss29 as the topmost differentially regulated genes in LIF-replaced FOXA2deficient mice that are explicitly expressed in the uterine glands (Kelleher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, uterine glands have direct connections to the developing placenta in mice (Arora et al, 2016; Yuan et al, 2018) and humans (Burton et al, 2002). Thus, products and secretions of endometrial glands are hypothesized to control development and growth of embryo and placenta throughout pregnancy (Dhakal et al, 2020; Kelleher et al, 2019).…”
Section: Introductionmentioning
confidence: 99%